Thermal, Structural and Flammability Characteristics of Polypropylene Composites Reinforced with Untreated Canarium schweinfurthii Nut-Shell Particles - Ago Mikyitsabu Atoshi; Garindo Boro; Martha Jimwan; Fildan Selbyen Comfort (Darul Yasin Al Sys, 2026)
The increasing demand for sustainable materials has intensified interest in converting agricultural residues into functional fillers for polymer composites. This study investigated the thermal, structural, and flammability characteristics of polypropylene (PP) composites containing untreated Canarium schweinfurthii nut-shell (CFN) particles. The particles were processed to a size of 45 µm and incorporated into PP at loadings of 0, 10, 15, 20, 25, and 30 wt.% using solvent casting. The resulting composites were characterized through density measurement, flame-propagation testing, Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). Composite density increased progressively with CFN loading. However, flame-propagation rates also increased at higher loadings, a response consistent with the combustible lignocellulosic composition of the particles and the generation of volatile degradation products. FTIR spectra displayed the characteristic functional groups of both PP and CFN, while the absence of new absorption bands indicated that filler–matrix interactions were predominantly physical. DSC revealed thermal events associated with moisture removal, PP crystallization, and degradation of the lignocellulosic constituents, demonstrating that CFN incorporation modified the matrix’s thermal response. XRD analysis confirmed that the characteristic α-crystalline structure of PP was retained after particle incorporation, although the degree of crystallinity varied with filler loading. These findings demonstrate that untreated C. schweinfurthii nut-shell particles can function as sustainable biofillers in PP composites for nonstructural applications. The study further establishes how CFN loading influences composite density, thermal behavior, crystallinity, and flame propagation, although the increased flammability at higher loadings should be considered in subsequent material development.